Antiretroviral therapy outcome in human immuno-deficiency virus infected patients in a tertiary care hospital - Manohar, Hasitha Diana; Shenoy, Smita; Varma, Muralidhar; Kamath, Asha; Malalur, Chaithanya; Bairy, Kurady Laxminarayana; Tilak, Amod; Saravu, Kavitha (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Human immunodeficiency virus (HIV) presently accounts for the highest number of deaths due to any infective agent in the world. The present study assessed the one year treatment outcome following antiretroviral therapy in HIV positive, treatment naïve patients in a tertiary care hospital. Methods: Adult HIV positive, antiretroviral treatment naive patients who were started on antiretroviral therapy (ART) between 1st January 2011 and 31st May 2013 were included in the study. Data was collected from their case records. CD4+cell count, haemoglobin level, weight, occurrence of opportunistic infections (OIs) and adverse drug reactions (ADRs) were analysed at baseline, 6 and 12 months following start of antiretroviral therapy. Data was analysed using parametric and nonparametric tests. Results: Data of 325 patients was analysed. Overall, the median increase in CD4+ count at 1 year after initiation of treatment was observed to be clinically significant. Patients on tenofovir based regimen showed a significantly greater increase in the median CD4+ count (P = 1.12×10-05) and haemoglobin (P = 0.002) as compared to those on non-tenofovir based regimen. A total of 151 ADRs were recorded in the study, of which the most common were skin rash 24%, anaemia and gastrointestinal side effects 17% each. Frequency of opportunistic infections gradually declined after ART. At the end of 1 year of treatment, the cumulative loss to follow up was 7.4%. Conclusions: By following the current national guidelines, the desired immunological and clinical response following initiation of ART can be achieved while minimizing drug toxicity.